2024
DOI: 10.3390/v16010107
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection and Phylogenetic Analysis of Tick-Borne Encephalitis Virus from Ticks Collected from Cattle in Kyrgyzstan, 2023

Haneul Jung,
Chi-Hwan Choi,
Minji Lee
et al.

Abstract: Ticks are important vectors of the tick-borne encephalitis virus (TBEV). In Kyrgyzstan, the livestock farming trade and nomadic lifestyle enable tick-borne diseases to be imported from neighboring countries, but there are few relevant studies. In this study, we collected 40 ticks from cattle in Kyrgyzstan. Molecular marker analysis identified the ticks as Ixodes persulcatus (97.5%; n = 39) and Haemaphysalis punctata (2.5%; n = 1). Real-time PCR screening revealed two ticks to be positive for TBEV, but only one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Although several studies of tick-borne pathogens have been reported in animal hosts in Kyrgyzstan, no information is available on using molecular tools to characterize their prevalence in ticks. The only pathogen identified in ticks is the tick-borne encephalitis virus (TBEV), which causes severe neurological disorders and is found in Ixodes persulcatus in the northern region [ 10 , 11 ]. Our investigation revealed that seven of the ten tick species including H. punctata , A. persicus , R. annulatus , R. turanicus , Demacentor spp., Hy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies of tick-borne pathogens have been reported in animal hosts in Kyrgyzstan, no information is available on using molecular tools to characterize their prevalence in ticks. The only pathogen identified in ticks is the tick-borne encephalitis virus (TBEV), which causes severe neurological disorders and is found in Ixodes persulcatus in the northern region [ 10 , 11 ]. Our investigation revealed that seven of the ten tick species including H. punctata , A. persicus , R. annulatus , R. turanicus , Demacentor spp., Hy.…”
Section: Discussionmentioning
confidence: 99%
“…Ticks are one of the major ectoparasitic arthropods affecting the health of domestic animals [ 5 , 6 ]. They may transmit a wide range of pathogens, including bacteria ( Anaplasma , Ehrlichia [ 7 ], Rickettsia [ 8 ]), viruses ( Dabie bandavirus [ 9 ] and Orthoflavivirus encephalitidis [ 10 , 11 ]), and protozoa ( Babesia and Theileria [ 12 , 13 ]). When large numbers of ticks feed on animals, they can reduce milk and meat production, thereby decreasing the value of domestic animals.…”
Section: Introductionmentioning
confidence: 99%